Effect of hypertonic saline on mucociliary clearance and clinical outcomes in chronic bronchitis. Issue 3 (11th August 2020) - Bennett, William D.; Henderson, Ashley G.; Ceppe, Agathe; Zeman, Kirby L.; Wu, Jihong; Gladman, Christine; Fuller, Fred; Gazda, Stephen; Button, Brian; Boucher, Richard C.; Donaldson, Scott H.
Background: Mucus dehydration and impaired mucus clearance are common features of cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD). In CF, inhaled hypertonic saline (HS) improves lung function and produces sustained increases in mucociliary clearance (MCC). We hypothesised that administration of HS (7% NaCl) twice daily for 2 weeks would improve clinical outcomes and produce sustained increases in MCC in COPD subjects with a chronic bronchitis (CB) phenotype. Methods: Twenty-two CB subjects completed a double-blinded, crossover study comparing inhaled HS to a hypotonic control solution (0.12% saline) administered via nebuliser twice daily for 2 weeks. Treatment order was randomised. During each treatment period, symptoms and spirometry were measured. MCC was measured at baseline, shortly after initial study agent administration, and approximately 12 h after the final dose. Results: HS was safe and well tolerated but overall produced no significant improvements in spirometry or patient-reported outcomes. CB subjects had slower baseline MCC than healthy subjects. The MCC rates over 60 min (Ave60Clr) in CB subjects following 2 weeks of HS were not different from 0.12% saline but were slower than baseline (Ave60Clr was 9.1±6.3% at baseline versus 5.3±6.9% after HS; p<0.05). Subgroup analyses determined that subjects with residual baseline central lung clearance (14 subjects) had improved spirometry and symptoms following treatment with HS, but not 0.12% saline, treatment. Conclusions: Inhaled HS appeared to be safe in a general CB population. A specific phenotypic subgroup may benefit from HS but requires additional study. 2-week HS treatment in CB does not lead to overall improvement in baseline mucociliary clearance. However, a subgroup of patients with residual, noncough-induced central airway clearance does show improvement in both spirometry and symptoms. https://bit.ly/36ji6Vn